2020
DOI: 10.3390/ma13235368
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Manufacturing Processes of Composite Form-Stable Phase Change Materials Based on Ca(NO3)2–NaNO3 and Expanded Graphite

Abstract: The fabrication of form-stable phase change materials (FS-PCMs) usually involves four manufacturing processes: mixing, immersion, stabilization, and sintering. In each process, the operation parameters could affect the performance of the fabricated PCM composite. To gain an efficient and low-cost method for large-scale production of the molten salts/expanded graphite (EG) composite FS-PCMs, the effects of different operating parameters were investigated, including the stirring speed, evaporation temperature, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Liu et al [31] also demonstrated that increasing the porosity or decreasing the pore size could effectively increase the infiltration ratio of inorganic salt. Both the sintering temperature and impregnation temperature during the preparation process affect the CPCMs' thermal properties [32]. The former is a key factor in regulating the pore structure of the ceramic carrier, while the latter ensures the loading.…”
Section: Process Flow For Mixed Impregnation [19] (Reprinted With Per...mentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [31] also demonstrated that increasing the porosity or decreasing the pore size could effectively increase the infiltration ratio of inorganic salt. Both the sintering temperature and impregnation temperature during the preparation process affect the CPCMs' thermal properties [32]. The former is a key factor in regulating the pore structure of the ceramic carrier, while the latter ensures the loading.…”
Section: Process Flow For Mixed Impregnation [19] (Reprinted With Per...mentioning
confidence: 99%
“…For the cold pressing-sintering process, the ratio between the materials, the amount of molding pressure, and the sintering temperature all have an important effect on the CPCMs' mechanical and thermophysical properties [40]. Qin et al [32,41] investigated the Na 2 SO 4 /diatomite CPCMs ratio. It was finally determined that CPCMs containing 45% diatomite were optimal in terms of energy density, leakage prevention, and mechanical strength.…”
Section: Energy Consumption Conversion Storage and Efficiencymentioning
confidence: 99%
“…Recent study shows that PCMs were prepared by molten salt/expanded graphite FSPCMs [93]. Molten salts, obtained from fusion of inorganic salt, are most promising fluids for storage of sensible and latent heat.…”
Section: Composite Pcm With Two Phase Transition Temperaturesmentioning
confidence: 99%
“…An important point is that because most fillers are chemically inert, the interface interaction with the polymer matrix is weak, resulting in poor dispersion of the filler in the matrix, a tendency of accumulation, and higher interface thermal resistance. In this case, optimization of the fillers’ thermal conductivity is not possible. Many strategies have been used to conduct surface modification of fillers. The coating nanolayer on the filler surface is considered an effective surface modification method to improve the interfacial bonding force between the filler and the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%